1998
DOI: 10.1161/01.atv.18.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Age-Related Increase in Central Arterial Stiffness in Physically Active Women

Abstract: Abstract-Increased arterial stiffness is thought to contribute to the increased incidence of cardiovascular disease with age.Little, however, is known about the influence of aging on central and peripheral arterial stiffness in females. Moreover, it is unknown whether physical activity status influences age-related increases in arterial stiffness in females. Arterial pulse wave velocity (PWV) and augmentation index (AI, applanation tonometry) were measured in 53 healthy females, including 10 premenopausal (Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
340
4
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 417 publications
(375 citation statements)
references
References 35 publications
25
340
4
6
Order By: Relevance
“…Those findings are consistent with our results. In some studies, PWV was only correlated with SBP, 20,21 but in others with both SBP and DBP. 22 Sa Cunha et al 23 suggested gender difference; SBP showed correlation with PWV in both genders, whereas DBP was correlated with PWV only in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those findings are consistent with our results. In some studies, PWV was only correlated with SBP, 20,21 but in others with both SBP and DBP. 22 Sa Cunha et al 23 suggested gender difference; SBP showed correlation with PWV in both genders, whereas DBP was correlated with PWV only in women.…”
Section: Discussionmentioning
confidence: 99%
“…Although BP is one of the strongest factors influencing PWV, varying correlation coefficients have been reported between the various PWV (aorta-leg-arm) and BP (systolic, diastolic, mean, pulse) using non-invasive methods. 5,[18][19][20][21][22][23][24] This variation may be attributable, at least in part, to the inherent variability of both PWV and BP within and across individual subjects and also to the method of BP 25 and PWV measurements.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, arterial stiffness and BP were negatively associated with cardiorespiratory fitness. 13 When considering the pathophysiological implications of vascular stiffening, it is also important not to overlook changes in the heart to which the blood vessels are coupled. In accordance with the concept of 'vascular-ventricular coupling' in that morphological and functional changes in the left ventricle and vasculature are closely coupled, we hypothesized that higher cardiorespiratory fitness is associated with the smaller age-related increases in arterial stiffness and BP, and that smaller increases attenuate LV remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Other studies reported that augmentation index was correlated to both SBP and DBP 20 or only to SBP. 21,22 Interestingly, Cameron et al 21 found in a study population of 262 hypertensive subjects that augmentation index was correlated to DBP only in males and that this relation was lost when augmentation index was normalised for age. There are also inconsistent results in studies only measuring mean blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that PWV was only correlated to SBP. 22,25 Others found that PWV was correlated to both SBP and DBP 18 or was correlated to SBP in both men and women, but was correlated to DBP only in women. 26 The controversial results reported in the literature may be attributed to the large variability in the population studied, such as the broad age range, gender distribution and the presence of different diseases or drug regimens.…”
Section: Introductionmentioning
confidence: 99%